Japanese Concept of Urban Promotion Control Area (UCA) to Save Agricultural Land in Bangladesh - Tariquzzaman, Sharif Mohammad (Journal of Bangladesh Institute of Planners, 2012)
Urban sprawling and unplanned infrastructure development are devouring productive land. Bangladesh is basically an agro based economy. In our country, about 1% of agricultural land in each year is transferred to another use. If this process continues all of our agricultural land would diminish within 100 years. This terrible situation is very crucial for an agro-based economy. In this paper, an attempt has been made to illustrate the necessity of introducing the Urban Promotion Control Area (UCA) in preparing physical development plan in Bangladesh to save agricultural land. This idea is well practiced in Japanese city planning. Unplanned development of physical infrastructure, especially development of unplanned road is the main cause of urban sprawling into the valuable agricultural land. The awful encroachment into the agricultural land also may cause haphazard urbanization. This type of land use regulation may protect the unpleasant encroachment into the UCA land. Public investment in UCA for urban infrastructure development could be strictly prohibited, so that unplanned development would be restricted. DOI: http://dx.doi.org/10.3329/jbip.v2i0.9570 Journal of Bangladesh Institute of Planners Vol. 2, December 2009, pp. 98-106